2001
DOI: 10.1007/s001250051667
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress impairs insulin internalization in endothelial cells in vitro

Abstract: Coexistence of insulin resistance and endothelial dysfunction is commonly observed in a variety of metabolic and cardiovascular disorders, including atherosclerosis and Type II (non-insulin dependent) diabetes mellitus [1]. Treatment of reduced insulin sensitivity with antioxidants, such as glutathione, vitamin C and vitamin E, can almost completely restore impaired endothelium-dependent vasorelaxation, a well established functional measure of endothelial dysfunction [2±4]. Because insulin sensitivity is susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 30 publications
(43 reference statements)
2
45
1
5
Order By: Relevance
“…Advanced glycation end products themselves bind transition metals (20), potentiating their toxic effects, including insulin resistance. Reactive oxygen species interfere with insulin signaling at various levels, impairing insulin uptake through a direct effect on insulin receptor function (21) and inhibiting the translocation of GLUT4 in the plasma membrane (22). Decreasing iron stores would ameliorate insulin resistance by reducing this cascade of events.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end products themselves bind transition metals (20), potentiating their toxic effects, including insulin resistance. Reactive oxygen species interfere with insulin signaling at various levels, impairing insulin uptake through a direct effect on insulin receptor function (21) and inhibiting the translocation of GLUT4 in the plasma membrane (22). Decreasing iron stores would ameliorate insulin resistance by reducing this cascade of events.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress induces both insulin resistance, by decreasing internalization of insulin (34), and increased ferritin synthesis. Factors related to hyperglycemia or oxidative stress can mediate in part the association between visfatin and parameters of iron metabolism (sTfR and prohepcidin) in subjects with altered glucose tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that AM deficiency induces insulin resistance in mice (35) and that acute hyperinsulinemia increases circulating AM levels in diabetic patients (36) or in uncomplicated obese subjects (37). In obese and/or diabetic patients, AM may, in turn, interact with the regulation of insulinemia (37)(38)(39)(40).…”
Section: Lean Population (Nz9)mentioning
confidence: 99%